PENERAPAN MODEL PEMBELAJARAN PBL MENGGUNAKAN MEDIA FLIPBOOK UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI SISWA SMAN AMBULU - Nira Virdarani (ScienceEdu, 2023)
This study aims to determine the increase in biology learning outcomes for class XI MIPA 1 SMAN Ambulu in the 2023/2024 academic year through the application of the Problem Based Learning (PBL) model using Flipbook media. This is interesting to study further because the learning process has not varied so that students are less enthusiastic and more easily bored so that it affects learning outcomes. This research is a classroom action research which consists of three cycles, namely pre-cycle, cycle I and cycle II. The subjects of this study were 36 students in class XI MIPA 1 at SMAN Ambulu. Sources of data obtained from observations, post-tests, and learning outcomes. Data analysis was performed using descriptive analysis techniques. After taking action using the PBL learning model using Flipbook media, it is known that the percentage of completeness of student learning outcomes has increased. The percentage of completeness of student learning outcomes during the pre-cycle was 56%, then in cycle I the percentage of completeness increased to 72%, then in cycle II the percentage of completeness again increased to 78% of the total number of 36 students. Based on the results of these data, it can be concluded that Flipbook media can improve student learning outcomes in class XI MIPA 1 SMAN Ambulu in biology subjects.